Quantification of Reproductive Disorders in Jersey, Hariana and Crossbred Dairy Cattle - SINGH, BALVIR; KUMAR, D; GHOSH, A K (The Indian Journal of Animal Reproduction, 2023)
On the basis of 3484 calving records of 811 Jersey, Hariana and crossbred cows, it was observedthat the per cent incidence of reproductive disorders among the progeny of different sires did not fallwithin the normal range of 30-70%. Susceptibility of prolapse, dystocia, retained placenta, metritis andabnormal bilth was 2.6, 3.0, 3.4, 3.0 and 3.6% in Jersey cows; 4.4, 5.7, 5.8, 5.6 and 6.6% in crossbredand 2.4, 3.1, 3.8, 2.9 and 3.5% in Hariana cows, respectively. Crossbred cattle were more susceptible tothese disorders than Hariana and Jersey cattle. These disorders were significantly associated with eachother. The skewness and kurtosis were absent for all the disorders in all the genetic groups except forprolapse and abnormal birth in Jersey cattle population.
Keywords: Cattle; Reproductive disorders; Association; Normality test; Chi-square; Kurtosis and skewness